(untitled) (Research, Society and Development, 2022)
Objective: Implement a reformulation of the therapeutic use antimicrobial form used by the HOL (Hospital Ophir Loyola), focusing on the rational use of restricted use antimicrobials in the Intensive Care Center (ICU). Methods: This is a quali-quantitative, cross-sectional and retrospective study, through data collection, using application forms for antimicrobials for restricted therapeutic use, from August to December 2018. Results: A total of 479 forms of request for antimicrobials for restricted therapeutic use in the ICU were evaluated. The main antimicrobials prescribed were: meropenem (n = 79; 16.5%), vancomycin (n = 60; 12.7%), piperacillin sodium + tazobactam sodium (n = 60; 12.5%), ceftriaxone (n = 50; 10.6%) and ciprofloxacin (n = 50; 10.6%) and the most consumed in DDD/1000 beds/day were: meropenem, fluconazole, vancomycin, ciprofloxacin, sodium piperacillin + sodium tazobactam and polymyxin B. The probable infectious diagnosis, justifying the antimicrobial request was sepsis (n = 124; 25.9%). Most patients were empirically indicated for medication (n = 396; 82.7%). The infectious agents, isolated in culture exams, more incidents were: acinetobacter baumanni and pseudomonas aeruginosa. In view of the results, the main changes were established in the components of the request form for antimicrobials for therapeutic use. Conclusion: This research proposed the restructuring of the form of antimicrobials for therapeutic use, in order to increase the control of the use of drugs of restricted use. Once in use, it will contribute to the optimization of the rational use of antimicrobials. The implementation of the adapted form, resulting as a product of this research, may be extended as a suggestion to professionals from hospital institutions who may be interested in initiating actions consistent with the antimicrobial use management program.